ANALYSIS OF THE STUDENTS’ PROBLEMS IN LEARNING VOCABULARY AT SMP SATAP PALEA - Ismail Ismail; Baharudin Baharudin; Sanaria Maneba (English Education Department, 2022)
The main problem of the research was ‘what are the problems faced by the students in learning vocabulary at the SMP Satap Palea?’ The research was case study. The subjects of the research were students and an English teacher in SMP Satap Palea at grade seven. The data of research were collected through test and interview. The data were analyzed through three steps adopted from Miles and Huberman; data reduction, data display and conclusion drawing. The result of this research showed that the result of test of the students of SMP Satap Palea was low. The problem faced by the students were lack or low motivation in learning English vocabulary, the students had low interest in learning English and lack of strategy used in learning vocabulary. It was indicated by the indifferent attitude or their reluctance to memorize English vocabulary. This reluctance impacted their mastery of English vocabulary. The students of SMP Satap Pelae rarely repeated their English lesson at home. The result of interview also indicated that student’s environment did not show positive impact for the students to learn, including the students peer.